Variability of Precipitating Ion Fluxes During the September 2017 Event at Mars. Issue 1 (30th January 2019) - Martinez, A.; Leblanc, F.; Chaufray, J. Y.; Modolo, R.; Romanelli, N.; Curry, S.; Luhmann, J.; Lillis, R.; Hara, T.; McFadden, J.; Halekas, J.; Eparvier, F.; et al.
Abstract: In this work, we study the influence of the September 2017 solar event on the precipitating heavy ion fluxes toward Mars' atmosphere as seen by Mars Atmosphere and Volatile EvolutioN/Solar Wind Ion Analyzer, an energy and angular ion spectrometer and by Mars Atmosphere and Volatile EvolutioN/Suprathermal and Thermal Ion Composition instrument, an energy, mass, and angular ion spectrometer. After a careful reconstruction of the background induced by the Solar Energetic Particle event in the Mars Atmosphere and Volatile EvolutioN/Solar Wind Ion Analyzer spectrometer, we investigate the precipitating ion flux responses to the space weather events that took place in September 2017. This period is a unique opportunity to analyze the respective role of various possible drivers of heavy ion precipitation into Mars' atmosphere with a wide range of different space weather events occurring during the same month. This study shows an increase in the precipitation flux by more than 1 order of magnitude during the arrival of the September Interplanetary Coronal Mass Ejection compared to the average flux during quiet solar conditions. We also showed that among the possible solar drivers, the solar wind dynamic pressure is the most significant during September 2017. Key Points: The solar wind dynamic pressure is the most significant during September 2017 set of space weather events An increase in the precipitating ion flux by more than one order during the arrival of the September interplanetary coronal mass ejection These results suggest that the EUV flux is not a key driver for the precipitating ion flux